PSYCHOLOGICAL MEANINGFULNESS SEBAGAI MEDIASI PENGARUH JOB CHARACTERISTICS TERHADAP EMPLOYEE ENGAGEMENT - Indriani Rusadi; Nasution Nasution (Management Insight: Jurnal Ilmiah Manajemen, 2021)
This study aims to determine the effect of job characteristics on employee engagement and psychological meaningfulness, as well as the effect of job characteristics on employee engagement mediated by psychological meaningfulness. This type of research is quantitative. The number of samples in this study were 180 respondents who were employees of PDAM Tirta Dharma Bengkulu. The results of this study explain that all hypotheses proposed in this study have a significant positive effect. The research findings explain that employee engagement is very high. These results explain that employee benefits can increase employee engagement with the company. Therefore, PDAM Tirta Dharma company needs to motivate and appreciate employee performance, as well as facilitate employees with a safe and comfortable environment to be able to further improve employee performance.